The Intricate Sea Borders of Batam (Indonesia), Tanah Merah (Singapore) and Johor Bahru (Malaysia) - Danny Faturachman; Dwi Nugroho (International Journal of Marine Engineering Innovation and Research, 2025)
this comprehensive report examines the technical specifications of passenger ferries operating in the busy maritime corridor between Batam (Indonesia), Tanah Merah (Singapore), and Johor Bahru (Malaysia), alongside the regulatory frameworks ensuring their safety in international waters. Predominantly high-speed catamarans equipped with waterjet propulsion systems (total power exceeding 4000 kW), these vessels accommodate 150-500 passengers and feature advanced safety systems including SOLAS-compliant life-saving appliances, GMDSS communication, ECDIS navigation, and automated fire suppression. Safety is governed by key IMO conventions such as SOLAS, STCW, and ISM Code, implemented nationally by Singapore's MPA (Merchant Shipping Act), Indonesia's DGST (Law No. 17/2008 on Shipping), and Malaysia's MDM (Merchant Shipping Ordinance 1952). Practical protocols encompass mandatory drills, STCW certified crew training, rigorous port state control inspections under Tokyo MOU, and incident analysis for continuous improvement. While robust oversight minimizes risks in high-traffic straits, challenges like human error and cross-border coordination underscore the need for enhanced trilateral cooperation. Findings highlight a mature safety ecosystem supporting millions of annual passengers, offering insights for nautical science education and policy refinement.